Decentralization's effects on education and health: Evidence from Ethiopia - Jean-Paul Faguet; Qaiser Khan; Devarakonda Priyanka Kanth (London School of Economics and Political Science (LSE), Department of International Development, 2019)
We explore the effects of decentralization on education and health in Ethiopia using an original database covering all of the country's regions and woredas (local governments). Ethiopia is a remarkable case in which war, famine and chaos in the 1970s-80s were followed by federalization, decentralization, rapid growth and dramatic improvements in human development. Did decentralization contribute to these successes? We use time series and panel data analyses to show that decentralization improved net enrollments in primary schools and access to antenatal care for pregnant women. The main channel appears to be institutional, not fiscal. We offer the database as an additional contribution.
Keywords: H41; H75; H77; O1; 330; Decentralization; Education; Health; Public investment; Ethiopia; Local government